Genomic and pathogenic analysis of a Muscovy duck parvovirus strain causing short beak and dwarfism syndrome without tongue protrusion. (December 2017) - Fu, Qiuling; Huang, Yu; Wan, Chunhe; Fu, Guanghua; Qi, Baomin; Cheng, Longfei; Shi, Shaohua; Chen, Hongmei; Liu, Rongchang; Chen, Zhenhai
Abstract: In 2008, clinical cases of short beak and dwarfism syndrome (SBDS) caused by Muscovy duck parvovirus (MDPV) infection were found in mule duck and Taiwan white duck farms in Fujian, China. A MDPV LH strain causing duck SBDS without tongue protrusion was isolated in this study. Phylogenetic analysis show that the MDPV LH strain was clustered together with other MDPV strains, but divergent from GPV isolates. Two major fragment deletions were found in the inverted terminal repeats (ITR) of MDPV LH similar to the ones in the ITR of MDPV GX5, YY and SAAS-SHNH strains. To investigate the pathogenicity of the MDPV LH strain, virus infection of young mule ducks was performed. The infected ducks showed SBDS symptoms including retard growth and shorten beaks without tongue protrusion. Atrophy of thymus, spleen and bursa of Fabricius was identified in the infected ducks. The results show that MDPV LH strain is moderately pathogenic to mule duck, leading to occurrence of SBDS. As far as we know, it is the first study showing that SBDS without tongue protrusion, and atrophy of thymus, spleen and bursa of Fabricius possibly associated with immunosuppression were found in the MDPV-infected ducks. The established duck-MDPV-SBDS system will help us to further work on the virus pathogenesis and develop efficacious vaccine against MDPV infection. Highlights: Identification of a MDPV strain causing SBDS symptoms without tongue protrusion in ducks; Atrophy of spleen, thymus and bursa of fabricius was found in the MDPV-infected ducks; Two major fragment deletions were determined in the ITR of some MDPV strains.